Sex, Age, and Bacteria: How the Intestinal Microbiota Is Modulated in a Protandrous Hermaphrodite Fish - Piazzon, M. Carla; Naya-Català, Fernando; Simó-Mirabet, Paula; Picard-Sánchez, Amparo; Roig, Francisco J.; Calduch-Giner, Josep A.; Sitjà-Bobadilla, Ariadna; Pérez-Sánchez, Jaume (Frontiers in Microbiology, 2019)
Intestinal microbiota is key for many host functions, such as digestion, nutrient metabolism, disease resistance and immune function. With the growth of the aquaculture industry, there has been a growing interest in the manipulation of fish gut microbiota to improve welfare and nutrition. Intestinal microbiota varies with many factors, including host species, genetics, developmental stage, diet, environment and sex. The aim of this study was to compare the intestinal microbiota of adult gilthead sea bream (Sparus aurata) from three groups of age and sex (1-year-old males and 2- and 4-year-old females) maintained under the same conditions and fed exactly the same diet. Microbiota diversity and richness did not differ among groups. However, bacterial composition did, highlighting the presence of Photobacterium and Vibrio starting at 2 years of age (females) and a higher presence of Staphylococcus and Corynebacterium in 1-year-old males. The core microbiota was defined by 14 OTUs and the groups that showed more OTUs in common were 2- and 4-year-old females. Discriminant analyses showed a clear separation by sex and age, with bacteria belonging to the phyla Firmicutes, Proteobacteria and Actinobacteria driving the separation. Pathway analysis performed with the inferred metagenome showed significant differences between 1-year-old males and 4-year-old females, with an increase in infection-related pathways, nitrotoluene degradation and sphingolipid metabolism, and a significant decrease in carbohydrate metabolism pathways with age. These results show, for the first time, how intestinal microbiota is modulated in adult gilthead sea bream and highlight the importance of reporting age and sex variables in these type of studies in fish.